2021
DOI: 10.3390/ijms22020505
|View full text |Cite
|
Sign up to set email alerts
|

Cudratricusxanthone A Inhibits Lipid Accumulation and Expression of Inducible Nitric Oxide Synthase in 3T3-L1 Preadipocytes

Abstract: Cudratricusxanthone A (CTXA) is a natural bioactive compound extracted from the roots of Cudrania tricuspidata Bureau and has been shown to possess anti-inflammatory, anti-proliferative, and hepatoprotective activities. However, at present, anti-adipogenic and anti-inflammatory effects of CTXA on adipocytes remain unclear. In this study, we investigated the effects of CTXA on lipid accumulation and expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2, two known inflammatory enzymes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…It is further documented that TNF-α is a strong inducer of COX-2 in various cells, including preadipocytes (15,16). Indeed, the authors of the present study as well as other groups have demonstrated that the short-term exposure of TNF-α leads to induction of COX-2 expression in 3T3-L1 preadipocytes (16)(17)(18). Thus, inhibition of the TNF-α-induced COX-2 expression in preadipocytes is considered as a possible target to manage obesity inflammation.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is further documented that TNF-α is a strong inducer of COX-2 in various cells, including preadipocytes (15,16). Indeed, the authors of the present study as well as other groups have demonstrated that the short-term exposure of TNF-α leads to induction of COX-2 expression in 3T3-L1 preadipocytes (16)(17)(18). Thus, inhibition of the TNF-α-induced COX-2 expression in preadipocytes is considered as a possible target to manage obesity inflammation.…”
Section: Introductionsupporting
confidence: 70%
“…A wealth of information illustrates that preadipocytes, the predominant cell types present in the AT, are able to express and secrete numerous pro-inflammatory cytokines [including TNF-α, interleukin (IL)-1β and IL-6] and enzymes (COX-2) (49-51), which can confer and aggravate obese inflammation, via the autocrine, paracrine and endocrine ways. As aforementioned, the authors and other groups have previously demonstrated that TNF-α is an inducer of COX-2 in not only 3T3-L1 preadipocytes but also in mature or differentiated adipocytes (15)(16)(17)(18)(19). To date, the regulation of pro-inflammatory cytokine-induced expression of COX-2 by LNX in 3T3-L1 preadipocytes remains unknown.…”
Section: Discussionmentioning
confidence: 89%
“…Of interest, it has been previously shown that TNF-α is a strong inducer of iNOS in many types of cells, including (pre) adipocytes [24]. Supporting this, we also have recently demonstrated the ability of TNF-α to induce iNOS expression in 3T3-L1 (pre)adipocytes [25]. However, at present, the inducer(s) and its regulation of iNOS expression in (pre)adipocytes remain unclear.…”
Section: Introductionsupporting
confidence: 62%
“…Aforementioned, we and others have previously shown that TNF-α, another pro-inflammatory cytokine, up-regulates the expression of iNOS in (pre)adipocytes [24,25]. Given that (pre)adipocytes express and secrete not only TNF-α but also other pro-inflammatory cytokines, and they are exposed to many endogenic and exogenic stimuli, we herein have investigated the effects of endogenic (IL-1β, IL-10, IL-12, IFN-γ) and exogenic (LPS) stimuli on the expression of iNOS in 3T3-L1 preadipocytes.…”
Section: Discussionmentioning
confidence: 95%